Natural rates in the New Synthesis: Same old trouble? - Hans-Michael Trautwein; Abdallah Zouache (Intervention. European Journal of Economics and Economic Policies, 2009)
This paper evaluates the concepts of natural rates of interest and output in Woodford's "neo-Wicksellian" and "benchmark New Keynesian" version of the New Neoclassical Synthesis (NNS) by comparing them with the original approach of Wicksell and critical assessments and adaptations by Lindahl, Myrdal, Keynes and Friedman. It is shown that the theoretical foundations of the NNS prescriptions for monetary policy are ambiguous and incomplete. Using the NNS definition(s) of the natural rate of output, New Keynesian policy rules do not necessarily yield results superior to those of "Old Keynesian" strategies of output stabilization. Moreover, natural rates of interest can hardly be defined independently of the influences of monetary policy. The use of natural-rate concepts in the NNS disregards essential problems that were identified in the older Wicksellian and Keynesian literature.
Keywords: E10; E30; E50; 330; natural rate; output gaps; interest-rate gaps; Wicksellian theory